Acronymizing eponyms: Where socio‑onomastic creativity outpacing morphological theory in naming male genitalia - Tur, Ajar Pradika Ananta (Universitas Ahmad Dahlan, 2026)
This study investigates how Indonesian Instagram users craft male genitalia eponyms through acronymization, arguing that this practice is governed not by morphological rules but by socio-onomastic constraints. Analysis of 62 distinct names which were collected via phenomenological netnography and coded against Kridalaksana's sixteen acronym categories reveals that only four categories are attested, with 83.8% of items clustering in the